A strategic action plan to enhance the accessibility of healthcare in rural areas of Zimbabwe - Manenji Mangundu; Lizeth Roets; Elsie Janse van Rensburg (Taylor & Francis Group, 2023)
Objective To identify strategies and develop a strategic action plan to enhance accessibility to healthcare in rural areas of Zimbabwe. Methods A cross sectional research approach with four (4) phases. Phase one (1) (quantitative), data was collected from professional nurses using self-administered questionnaires, healthcare users using interview questionnaires. Phase two (2) (qualitative), information was collected from a nominal group of national health directors leading to development strategic action plan in Phase three (3) informed by Phases 1 and 2, systems model and literature control. Strategic action plan was finalised and validated by members of the Parliamentary Portfolio Committee on Health in Phase 4. Settings Two districts (Masvingo and Chegutu) in two provinces (Masvingo and Mashonaland West) were involved. Participants Conveniently sampled professional nurses (90) and healthcare users (445) using the sampled public health facilities (Phase 1); conveniently sampled national health coordinators (five) (Phase 2); and all five members of the Parliamentary Portfolio Committee on Health (Phase 4). Research findings The strategic action plan focused on improving the health infrastructure; providing medical drugs, health workers and medical equipment; addressing shortages; and improving the capacity of the healthcare system. Conclusion Active participation at all levels (professional nurses, healthcare users, national health directors and members of parliament) allowed the development of a strategic action plan.